(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Background & Objectives: Poisoning is one of the most commonly encountered cause of death in medico legal autopsies. Diagnosis of poisoning is based on post-mortem examination and chemical analysis of viscera. Chemical analysis of viscera by FSL is time consuming process and sometimes it cannot detect poison. Present study can be helpful there to make diagnosis of poison from histopathological findings of upper gastrointestinal tract. Methods: Present study was conducted on randomly selected 150 cases of poisoning from total autopsies performed in year 2012 at department of forensic medicine, PDU govt. medical college, Rajkot. Histopathological findings like pale, congestion, haemorrhage, flatten rugae, edema, inflammatory cells, necrosis changes were noted. Results: In all cases of poisoning, irrespective of type of poison, in upper gastrointestinal tract, on histopathological examination, necrosis is observed in 74.66% cases followed by haemorrhage in 43.33% cases followed by acute inflammatory cells infiltrate in 42.66% cases. Interpretation & Conclusions: On the basis of the histopathological findings of upper gastrointestinal tract, combining with other data (history, clinical findings, gross